Determination of illegal and toxic ingredients in face creams - Mehlala, Nandipha (Department of Medicine, 2026)
The increasing prevalence of counterfeit and substandard face creams on the market poses significant risks to consumer health, with some products containing illegal and toxic ingredients that can lead to serious dermatological and systemic effects. This study focuses on the identification and quantification of illegal and toxic ingredients in fifty-eight skin cosmetic creams marketed to reduce pigmentation. Samples that were selected were those labelled as ‘'Skin lightening'', Skin brightening'', Skin whitening,” or “even tone” creams, purchased from local vendors within the Cape Town Metropolis, and from an online store. This study employed advanced analytical techniques to assess the potential health risks of face creams. The High-Pressure Liquid Chromatography (HPLC) method was used to determine thirteen compounds of interest such as hydroquinone, kojic acid (KA), and steroids. Secondly, Inductively Coupled plasma mass spectrometry (ICP-MS) assisted with MARS 6 digester was employed to determine metals (mercury, lead, chromium, nickel, cadmium, arsenic, etc.). Lastly, the study assessed potential health risk of the actives and metals through predictive risk assessment models developed by United States Environmental Protection Agency (USEPA). The health risk models consider active concentration (at 95% confidence level), and the unique properties of active or metal. The United States Environmental Protection Agency calculates carcinogenic cancer risk of metals using the Cancer Slope Factor (CSF) and the Average Daily Dose (ADD). The ADD is determined based on the concentration of the metal, intake rate, exposure frequency and duration, body weight, and averaging time. The cancer risk is then calculated by multiplying the ADD by the CSF, which represents the probability of developing cancer per unit of exposure. Risks are typically expressed as a probability (e.g., 1 in 10,000) and are compared to acceptable thresholds, usually ranging from 10−6 to 10−4. This assessment accounts for the metal's carcinogenic properties, exposure pathways and population sensitivities to evaluate potential health impacts. The analysis of face cream samples revealed the presence of eleven active compounds, including several illegal and toxic substances. Steroids were the most prevalent, detected in approximately 45% of the samples, with Clobetasol propionate (CP) being the predominant steroid, accounting for 68% of the steroid detections. Other steroids identified included Cortisone, Betamethasone Dipropionate (BD), Betamethasone (BM), and Fluocinolone, found in 12%, 12%, 4%, and 4% of the samples, respectively. Hydroquinone (HQ) was present in 16% of the samples, with concentrations ranging from 0.096% to 4.301%, particularly high in imported products. Arbutin, a derivative of HQ, was detected in 7% of the samples, while 4- phenoxy phenol appeared in 5% of the samples. Kojic Acid (KA) was found in 19% of the samples. Additionally, 4-butyl resorcinol, a potent tyrosinase inhibitor, was present in 59% of the samples, and 4-hydroxybenzoic acid, a common preservative, was detected in 43%. Heavy metals results provided a comprehensive insight into the presence of thirteen heavy metals (As, Cd, Cu, Cr, Co, Fe, Mn, Ni, Pb, V, Zn, Se, and Sb). Most samples contained multiple heavy metals, indicating a wide spread of occurrence across the tested products. Lead (Pb) was detected in forty-six samples (79.3%) at concentrations ranging from 0.001-15.41 ppm. Notably two samples, Chadni whitening cream and Rico had high concentrations at 3.71 ppm and 15.42 ppm respectively, above the threshold limit of 0.5 ppm. Mercury results were in the majority (85.75%) of samples exceeded the 1ppm safety threshold set by regulatory bodies. Products from Pakistan, China, India, and other countries were found to contain high mercury levels, with two samples, Omni Gold and Sandal, exhibiting exceptionally high concentrations. Notably, 55.4% of samples had mercury below 10 ppm, while 41.1% had levels in the tens to hundreds of ppm. Health risk assessment results indicated that hazard quotient levels were low, and the carcinogenic risk (CR) values for all detected metals were less than 1. Chromium (Cr) and Nickel (Ni) were the primary contributors to higher CR values. These findings highlight significant concerns regarding the presence of harmful substances in face creams, emphasizing the need for rigorous regulatory oversight. The health risk results for hydroquinone showed that seven samples, including Natural Glow Carotone (4.68 x 10⁻⁵), Coco Pulp (4.30 x 10⁻⁵), and Light & Bright (3.42 x 10⁻⁵), exceeded the CR threshold of 1 x 10⁻⁶ - that is, more than 1 in 1,000,000 persons was likely to develop cancer from continuous use of hydroquinone over the calculated period (70 years). These elevated CR values suggest a carcinogenic risk, with Natural Glow Carotone posing the highest risk among the tested samples. The hazard quotient values for creams containing mercury (ranging from 3.8 x 10−4 to 1.17 x 10−1 (0.117), were all below 1, indicating that the mercury content in these samples is unlikely to pose significant non-cancer health risks. Carcinogenic risk (CR) was below 1 x 10⁻⁶ for twenty -five samples (44%). However, thirty-three samples (56%) exceeded the cancer risk threshold of 1 x 10⁻⁶. Products with CR values above this threshold are considered unsafe for regular use, as they may expose consumers to potentially harmful levels of carcinogenic substances over time. Nine of the creams that contained hydroquinone also contained mercury. The calculated carcinogenic risk (CR) for hydroquinone was comparable higher than those of mercury, implying a greater contribution from hydroquinone to the overall risk from using the cream.